Do 18th century ‘bubbles’ survive the scrutiny of 21st century time series econometrics? - Hu, Y.; Oxley, Leslie (Elsevier, 2018)
Applying the methods of Phillips et al. (2015, PSY), while considering the possibility of non-stationary volatility (Harvey et al., 2016), evidence of exuberance in share prices is confirmed for the South Sea Company, and established for a number of other 18th century financial organisations, for the first time. The timings of these bubble episodes show signs of possible contagion.